Critique and resistance: What are the possible trenches? - Campana Alabarce, Melisa (Critical Proposals in Social Work, 2021)
The aim of this paper is to contribute to the theoretical-epistemological, as well as ethical-political discussion of two key categories of Critical Social Work, such as critique and resistance. To do that, it analyses three sets of problems, from which the three sections of the text are organized: I. Subject and subjection: the problem of the series autonomy-guardian-responsibility; II. Affections, alliances: the problem of inventing the common; III. De-colonizing pain and joy: the problem of the imperative of happiness.